People-centered entrepreneurship: The impact of empathy and social entrepreneurial self-efficacy for social entrepreneurial intention - Jung-Rae Kim (Global Business & Finance Review (GBFR), 2022)
Purpose: This study aims to examine the impact of empathy on social entrepreneurial intention. This study also investigates the mediating role of social entrepreneurial self-efficacy on the relationship between empathy and social entrepreneurial intention. Design/methodology/approach: Questionnaires were employed to collect data from future social entrepreneurs. A total of 250 completed questionnaires were returned. Multiple regression analysis was used to test the hypothesis. Findings: Results showed that empathy and social entrepreneurial self-efficacy were positively related to social entrepreneurial intention. Further, the link between empathy and social entrepreneurial intention was mediated by social entrepreneurial self-efficacy. Research limitations/implications: This study empirically confirmed that empathy and social entrepreneurial selfefficacy are important drivers of social entrepreneurial intention and also need to make an educational program that can increase the level of empathy and social entrepreneurial self-efficacy. Future studies may extend existing research by adopting other factors for the mediation mechanism. Originality/value: This study is one among few studies to identify the mediating effect of social entrepreneurial self-efficacy on the relationship between empathy and social entrepreneurial intention by examining Korea's unique dataset an Asia-Pacific country. Therefore, gaining insight from Asia-pacific country that empathy, social entrepreneurial self-efficacy positively affects social venture creation is valuable for broadening the social entrepreneurial intention research.
Keywords: 650; Empathy; Social entrepreneurial self-efficacy; Social entrepreneurial intention; Future social entrepreneur